Kompetencje dyrektora szkoły jako lidera. Raport z badań - Błajet, Piotr; Przyborowska, Beata; Murawska , Iwona (Studia Edukacyjne, 2017)
The text presents the assumptions and effects of realization of the novelty scheme of educating education leaders. The studies were realized on the basis of the authorial, innovative and integral education model. Ken Wilber’s integral model is used in creation of syllabuses in many schools and universities around the world. The results of implementation of our integral model are currently being formulated. Selected results are presented in the following report.